2022
DOI: 10.1590/s2175-97902022e201183
|View full text |Cite
|
Sign up to set email alerts
|

S-allyl Cysteine and Taurine revert peripheral metabolic and lipid profile in non-insulin-dependent diabetes mellitus animals: Combination vs Monotherapy

Abstract: The present study was designed to evaluate the beneficial synergistic effects of S-allyl Cysteine (SAC) and Taurine (TAU) on hyperglycemia, lipid profile and renal damage markers in type 2 diabetes mellitus (T2DM) in rats. Experimental T2DM was developed by administering an intraperitoneal single dose of nicotinamide (NA; 230 mg/kg) and streptozotocin (STZ; 65 mg/ kg) in adult rats. Control and diabetic rats were treated with SAC (150 mg/kg); TAU (200 mg/ kg) or SAC and TAU (75+100 mg/kg) combination for four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In our previous in vitro study, SAC and TAU combination was reported to have strong antioxidant and antidiabetic properties, indicating its potential for treating hyperglycemia and related complications (Rais, Ved, Ahmad, Parveen, & Mujeeb, 2021). According to an in vivo study, giving TAU and SAC-derivative (N-acetylcysteine) to male Sprague Dawley rats restored metabolic markers as a result of their strong antioxidant properties, which they exhibited through preventing oxidative reactions (Haber et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous in vitro study, SAC and TAU combination was reported to have strong antioxidant and antidiabetic properties, indicating its potential for treating hyperglycemia and related complications (Rais, Ved, Ahmad, Parveen, & Mujeeb, 2021). According to an in vivo study, giving TAU and SAC-derivative (N-acetylcysteine) to male Sprague Dawley rats restored metabolic markers as a result of their strong antioxidant properties, which they exhibited through preventing oxidative reactions (Haber et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…After the administration of NA/STZ, the animals were permitted standardized food and water access ad libitum . Blood glucose was evaluated after two days, and the animals with glucose level ≈140 ± 8 mg/dl were categorized as diabetics and recruited for further investigation (Masiello et al ., 1998; Rais et al ., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations